2012
DOI: 10.1371/journal.pone.0038085
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Non-Apoptotic Role for Scythe/BAT3: A Functional Switch between the Pro- and Anti-Proliferative Roles of p21 during the Cell Cycle

Abstract: BackgroundScythe/BAT3 is a member of the BAG protein family whose role in apoptosis has been extensively studied. However, since the developmental defects observed in Bat3-null mouse embryos cannot be explained solely by defects in apoptosis, we investigated whether BAT3 is also involved in cell-cycle progression.Methods/Principal FindingsUsing a stable-inducible Bat3-knockdown cellular system, we demonstrated that reduced BAT3 protein level causes a delay in both G1/S transition and G2/M progression. Concurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 64 publications
(125 reference statements)
0
14
0
1
Order By: Relevance
“…BAT3 is a nucleo-cytoplasmic shuttling protein that contains an N-terminal ubiquitin homology region, a zinc finger-like domain, a nuclear export signal (NES), an NLS and, in its C-terminal part, a BAG domain that binds to the ATPase domain of HSC70/HSP70. We and others have shown that BAT3 targets the acetyltransferase p300 [ 28 ] and p21 [ 34 ] to the nucleus. We therefore investigated whether BAT3 binds to Cath-D by GST pull-down assay.…”
Section: Resultsmentioning
confidence: 99%
“…BAT3 is a nucleo-cytoplasmic shuttling protein that contains an N-terminal ubiquitin homology region, a zinc finger-like domain, a nuclear export signal (NES), an NLS and, in its C-terminal part, a BAG domain that binds to the ATPase domain of HSC70/HSP70. We and others have shown that BAT3 targets the acetyltransferase p300 [ 28 ] and p21 [ 34 ] to the nucleus. We therefore investigated whether BAT3 binds to Cath-D by GST pull-down assay.…”
Section: Resultsmentioning
confidence: 99%
“…a relocation of p300 from the cytosol to the nucleus during starvation. BAT3 is also involved in p21 nuclear translocation during G2/M phases, followed by its degradation during the transition between the G1 and S phases (18); however, the mechanism responsible for BAT3 nuclear shuttling remains elusive. A recent study showed that BAT3 variants are generated by alternative splicing of exon11B, leading to a different pattern of expression and intracellular localization.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty five µl of RT-PCR mixture contained 10 µl of RNase free H O, 5 µl of 5 × buffer, 2 µl of 10 mM dNTP, 100 nmol/l of each primer and 1 µg RNA. The following primers were employed in semi-quantitative RT-PCR analysis: p21 [24,30] forward primer: 5'-AGCAGAGGAAGA-CCATGTGGAC-3' and p21 reverse primer: 5'-TTT-CGACCCTGAGA GTCTCCAG-3' p53 forward primer: 5'-TGCGTGTGGAGTATTTG GATG-3' and p53 reverse primer: 5'-TGGTACAGTCAGAGCCAA-CCAG-3'; b-actin [5] forward primer: 5'-AACAGT-CCGCCTAGAAGCAC-3' and b-actin reverse primer: 5'-CGTTGACATCGTAAAGACC-3'. The amplified products were size-fractionated by electrophoresis on 1.5% agarose gel, and analyzed by a FluorChem 8000 system with a software (Alpha Innotech, Santa Clara, CA, USA).…”
Section: Semiquantitative Rt-pcrmentioning
confidence: 99%